Microfluidic devices in nanotechnology. - Kumar, C. S. S. R. (Challa S. S. R.) (Wiley, 2010)
Nanotechnology, especially microfabrication, has been affecting every facet of traditional scientific disciplines. The first book on the application of microfluidic reactors in nanotechnology, Microfluidic Devices in Nanotechnology provides the fundamental aspects and potential applications of microfluidic devices, the physics of microfluids, specific methods of chemical synthesis of nanomaterials, and more. As the first book to discuss the unique properties and capabilities of these nanomaterials in the miniaturization of devices, this text serves as a one-stop resource for nanoscientists int.